IMPROVING THE MANAGEMENT SYSTEM OF PRIVATE HIGHER EDUCATION INSTITUTIONS BASED ON THE EXPERIENCE OF ASIAN COUNTRIES (International Congress on Economics, Management and Business Studies, 2026)
This thesis analyzes the management experience of private higher education institutions in Asian countries, their organizational and economic mechanisms, and development factors. In particular, the approaches of countries such as Japan, South Korea, Singapore, Malaysia, and China in developing the private higher education system are examined. Furthermore, the study highlights opportunities for applying advanced practices aimed at improving management efficiency in private higher education institutions, ensuring academic autonomy, strengthening education quality control, and implementing innovative management models.
Keywords: private higher education institutions, educational management, academic governance, strategic management, financial sustainability, international experience, Asian model, innovative education.